An Alternative Solution of Train-Track Dynamic Interaction - Zhaowei Chen; Hui Fang (Shock and Vibration)
Train-track interaction (TTI) is a classic research topic in railway engineering, which consists of three main parts, namely, train model, track model, and wheel-rail interaction. To improve the computational accuracy and broaden the application range, an alternative calculation method to investigate TTI based on secondary development technology of the commercial software ANSYS through APDL language is introduced in this article. Primarily, the train-track interaction theory is briefly presented. On this basis, TTI is programmed and implemented on the computing platform of ANSYS by fully taking the nonlinear wheel-rail interaction into consideration. In this calculation method, the train model, which is established based on multibody dynamics theory and solved by an advanced explicit integration method, is programmed into ANSYS through APDL language, while the track part is simulated according to finite element theory. Then, the proposed calculation method is validated with field test results to verify the validity. Finally, a numerical demonstration is conducted employing the present method. Results show that the introduced method is effective and able to investigate TTI. Different complicated track systems can be accurately simulated employing this method. Moreover, this method is also adoptable to explore train-bridge interaction and train-track-bridge interaction.